Comprehensive insights into evaluation and benchmarking of real-time skin detectors: review, open issues & challenges, and recommended solutions - M.Yas, Qahtan (N/A, 2017)
Comprehensive insights into evaluation and benchmarking of real-time skin detectors: review, open issues & challenges, and recommended solutions by M.Yas, Qahtan